Cultural Heritage and Creative Industries in Ensuring Sustainable Development: Ukrainian Experience - Hurova, Inna; Dodonov, Roman; Matvieiev, Vitalii; Binkivska, Kristina; Kondratyuk-Antonova, Tetyana; Strokov , Igor (European Journal of Sustainable Development, 2024)
This article investigates the instrumental role of cultural heritage and creative industries in driving sustainable development, drawing empirical insights from the Ukrainian context. Anchored in UNESCO's normative frameworks, the study elucidates how preserving tangible and intangible cultural assets fosters identity formation, social cohesion, and economic vitality, thereby catalysing progress across the triple bottom line of sustainability. Complementing a comprehensive literature review with primary data from a student survey, the analysis spotlights Ukraine's initiatives to integrate heritage and creativity into national development strategies, spearheaded by the Ukrainian Cultural Foundation. Amidst Russia's ongoing assault on Ukrainian culture, the research underscores the urgency of safeguarding cultural legacies as cornerstones of societal resilience and identity preservation. Keywords: sustainable societal development, culture, cultural heritage, creative industries, Ukrainian Cultural Foundation, museum